Heat-unstable apple pathogenesis-related proteins alone or interacting with polyphenols contribute to haze formation in clear apple juice. (30th March 2020) - Millet, Melanie; Poupard, Pascal; Guilois-Dubois, Sophie; Poiraud, Arnaud; Fanuel, Mathieu; Rogniaux, Helene; Guyot, Sylvain
Highlights: Unambiguous presence of pathogenesis-related proteins (PRP) in apple juice haze. Involvement of heat-unstable proteins in the formation of haze. Apple juice procyanidin oligomers interact with PRPs to form complexes. Interactions were greater when the degree of polymerization of tannins increased. Abstract: Physico-chemical instability is a damaging defect that can occur in clear bottled beverages leading to the formation of haze. In a previous study, we showed the presence of proteins in haze gathered from apple juices. For the first time, proteomics was used to sequence and identify four pathogenesis-related proteins (PRPs) from the haze of a commercial apple juice. Then, a study involving purified PRPs and polyphenols from apple juice was conducted in model solution to understand the mechanisms by which they are involved in haze formation. Visual assessment revealed that apple juice pathogenesis-related proteins are able to form haze alone when thermally denatured. These proteins were also able to interact with apple juice procyanidins to form complexes that can be precipitated using ultracentrifugation, even without prior heating. These interactions were greater when the degree of polymerization of tannins increased.